1994
DOI: 10.1016/0045-6535(94)90428-6
|View full text |Cite
|
Sign up to set email alerts
|

PCB and dioxin levels in plasma and human milk of 418 dutch women and their infants. Predictive value of PCB congener levels in maternal plasma for fetal and infant's exposure to PCBs and dioxins

Abstract: Polychlorinated biphenyls (PCBs) as well as dioxins (polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs)) are potentially hazardous compounds in the environment for human beings. In order to investigate PCB and dioxin exposure of Dutch women and their neonates, levels were examined in 418 mother-infant pairs. Four non-planar PCB congener levels (PCB 118, 138, 153 and 180) were measured in maternal plasma and in umbilical cord plasma. The 209 mothers who breast-fed their infants collected human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 13 publications
10
58
3
Order By: Relevance
“…Associations described previously among ΣPCBs and specific PCB congeners were confirmed in these analyses (De Voto et al 1997;Koopman-Esseboom et al 1994). Strong correlations were observed between ΣPCBs with PCB congeners 153 and 138, and with the three groupings of PCBs (r > 0.9, p-values < 0.0001).…”
Section: Resultssupporting
confidence: 61%
“…Associations described previously among ΣPCBs and specific PCB congeners were confirmed in these analyses (De Voto et al 1997;Koopman-Esseboom et al 1994). Strong correlations were observed between ΣPCBs with PCB congeners 153 and 138, and with the three groupings of PCBs (r > 0.9, p-values < 0.0001).…”
Section: Resultssupporting
confidence: 61%
“…The total cord serum concentration of PCBs averaged 0.54 ng/g, with a median of 0.38 ng/g. The concentrations of key individual congeners (PCBs 118, 138, 153, and 180) were about one-half the concentrations reported in the Dutch cohort (Koopman-Esseboom et al 1994a). The levels in the New Bedford cohort are, however, quite similar to those reported in the Oswego, New York, fish-exposure cohort.…”
Section: The New Bedford Cohortmentioning
confidence: 51%
“…As Koopman-Esseboom et al (1994a) have shown, the levels of the various PCB and PCDD/PCDF congeners in human tissues are highly intercorrelated. This will undoubtedly complicate any attempts to determine structure-activity relationships based on human data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, numerous studies have tried to develop a more costefficient assessment of dioxin exposure. Most studies have adopted the use of PCB congeners in breast milk as markers for dioxin measurement (Glynn et al, 2001;Koopman-Essebom et al, 1994). However, the association between concentrations of PCB markers and dioxin may vary among individual study populations with different geographical and cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%